Beyond fluid intelligence and personality traits in social support: the role of ability based emotional intelligence - Fabio, Annamaria Di (Frontiers in Psychology, 2015)
Social support represents an important individual resource that has been associated with multiple indices of adaptive functioning and resiliency. Existing research has also identified an association between emotional intelligence (EI) and social support. The present study builds on prior research by investigating the contributions of ability based emotional intelligence to social support, beyond the effects of fluid intelligence and personality traits. The Advanced Progressive Matrices (APM), the Big Five Questionnaire (BFQ), the Mayer Salovey Caruso Emotional Intelligence test (MSCEIT), and the Multidimensional scale of Perceived Social Support (MSPSS) were administered to 149 Italian high school students. The results showed that ability based EI added significant incremental variance in explaining perceived social support, beyond the variance due to fluid intelligence and personality traits. The results underline the role of ability based emotional intelligence in relation to perceived social support. Since ability based emotional intelligence can be increased through specific training, the results of the present study highlight new possibilities for research and intervention in a preventive framework.